Lightning Arrester Analysis at Pandu 150 Kv Substation - Janne Deivy Ticoh; Nontje Sangi; Ridwani; Benjamin Limbong Tampang; Muzaina (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The process of distributing electricity from the substation to the consumers often occurs interference, electrical interference at the station caused by two factors that are internal factors and external factors. Internal factors such as lack of good equipment, while external factors such as human error and natural disturbances such as lightning, earthquakes, flood, wind and others. Safety protection system on electrical equipment of Pandu substation. Surge arresters play an important role in Pandu substations to limit switching overvoltages and lightning strikes, followed by overvoltages from lightning current to earth. the efficiency of the arrester is a function of the distance from its location to the protected equipment, the maximum system voltage achieved is 165 kilo vot, the arrester`s rated voltage is 132 kilo volt line impedance /conductor 475,764 ohms, air insulation breakdown voltage 1515.8 kilo voltv, arrester discharge current 4.27 kilo ampers and an optimal distance between arrester and transformer 10.96 meters.